Acceptability of emergency contraception in Brazil, Chile, and Mexico: 1 - Perceptions of emergency oral contraceptives Aceitabilidade da anticoncepção de emergência no Brasil, Chile e México: 1 - Percepções sobre as pílulas de anticoncepção de emergência - Soledad Díaz; Ellen Hardy; Gloria Alvarado; Enrique Ezcurra (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
This article presents the results of a study on the acceptability of emergency contraception (EC) in Brazil, Chile, and Mexico. Opinions of potential users and possible providers were obtained through discussion groups and those of authorities and policy-makers through semi-structured interviews. Most participants had a positive opinion of EC, based on the view that it can help reduce unplanned pregnancy, adolescent pregnancy, and unsafe abortion. Several interviewees felt that all women should be informed about EC, while others viewed it as a method for special situations such as rape and unprotected first sexual intercourse. Concern was expressed that its introduction might be associated with a decrease in condom use, increase in sexually transmitted diseases, and irresponsible or promiscuous sexual behavior among adolescents. The need for EC was clearly perceived by most participants, leading to the conclusion that health authorities have the responsibility of implementing programs for its introduction. Training of health care personnel should include the discussion of reproductive health problems that could be prevented by EC. Apresentam-se opiniões de potenciais usuárias e possíveis provedores de anticoncepção de emergência (AE) no Brasil, Chile e México. As opiniões foram obtidas em grupos de discussão, e a opinião de autoridades e outras pessoas influentes por meio de entrevistas semi-estruturadas. A maioria teve uma opinião positiva sobre a AE, que poderia contribuir para reduzir gravidez não planejadas, o aborto provocado e a gravidez entre adolescentes. Alguns consideraram que todas as mulheres deveriam saber sobre a AE, enquanto outros pensaram que era um método para situações especiais, tais como estupro e uma primeira relação sexual desprotegida. As preocupações foram de que sua introdução poderia estar associada à diminuição do uso do condom, aumento das doenças de transmissão sexual e comportamento sexual irresponsável de adolescentes. A necessidade da AE foi percebida pela maioria dos participantes, levando à conclusão de que as autoridades de saúde devem implementar sua introdução e treinar os profissionais de saúde, incluindo a discussão dos problemas de saúde reprodutiva que poderiam ser resolvidos pela AE.